microRNA Prognostic Signature for Postoperative Success of Metastatic Orthopedic Cancers: Implications for Precision Microsurgery - Xu, Shi-Bao; Fan, Rong-Hao; Qin, Xiao; Han, Rui-Ming (Frontiers in Cell and Developmental Biology, 2021)
The importance of miRNA prognostic signature in cancer, particular cancer metastasis is increasingly being realized. Bone metastasis from several primary human cancers can be managed in clinics by surgical intervention but the prognostic impact of miRNA signature on post-surgery outcome of patients is unknown. This study evaluated a miRNA signature for post-operative outcome of patients with bone metastatic disease. First, the miRNAs, miR-135, miR-203, miR-10b, miR-194, miR-886, and miR-124 were evaluated in bone metastatic tissues, relative to adjacent control tissue. The cohorts of samples (n = 44) consisted of bone metastatic cancer patients with primary lung (n = 18) or breast cancer (n = 26). miR-203 was significantly down-regulated while miR-10b was significantly up-regulated in bone metastasis. Additionally, miR-135 was significantly differentially expressed in the primary lung cancer patients while miR-194 in primary breast cancer patients. The low miR-203- high miR-10b expression was designated high risk group and, compared to the low risk group (high miR-203-low miR-10b expression). Patients with the signature high risk fared significantly better with surgical intervention, in terms of survival at 12 months time point (40% survival with surgery vs. 10% survival without surgery), as revealed by retrospective analysis of patient data. This work reveals potential utilization of miRNA expression levels in not only the general prognosis of cancer metastasis but also the prognosis of surgical intervention with implication for better stratification of patients.